Correction: Performance of resistive index and semi-quantitative power doppler ultrasound score in predicting acute kidney injury: A meta-analysis of prospective studies. - Yu Zhu; Weifeng Zhen; Xiaoning Zhang; Zhenhua Shi; Ling Zhang; Jiuju Zhou; Qiong Wei (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0270623.].